2(v-5)-4=-5(-3v+2)-3v

Simple and best practice solution for 2(v-5)-4=-5(-3v+2)-3v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(v-5)-4=-5(-3v+2)-3v equation:


2(v-5)-4=-5(-3v+2)-3v

We simplify the equation to the form, which is simple to understand
2(v-5)-4=-5(-3v+2)-3v

Reorder the terms in parentheses
+(+2v-10)-4=-5*(-3v+2)-3v

Remove unnecessary parentheses
+2v-10-4=-5+*(-3v+2+)-3v

Reorder the terms in parentheses
+2v-10-4=+(+15v-10)-3v

Remove unnecessary parentheses
+2v-10-4=+15v-10-3v

We move all terms containing v to the left and all other terms to the right.
+2v-15v+3v=-10+10+4

We simplify left and right side of the equation.
-10v=+4

We divide both sides of the equation by -10 to get v.
v=-0.4

See similar equations:

| 11.2x=556 | | 11+[-3c]-4c= | | 3/x-1/3=1/4 | | 9+1.2(7n-26)-8n= | | b-1.6/4=3 | | -3+x^2=50 | | 4c/3=6c-112 | | 7y-2.2=3y | | 5/12(x-5)=3 | | 18.2x=1820 | | 2n+(-6)=2n-5 | | 1/4x3/7x4/5= | | 8x-3x+99=8x+36 | | 11c-16=-6-c+12c | | 7a/=4a-117 | | 6b+3b+14= | | 5n/4=4n-44 | | 5w^2+2w-7=0 | | 54-11x=16+8x | | x+0.75x=91 | | 4w-63=7w/4 | | -11+10p+100=4-10p-11 | | 10x-5=x-2 | | 5z/3=3z-20 | | 5x^2-10=25 | | 24+30x= | | 11z=8+10 | | 7x-5=2(3x+9) | | 3x+5x-3=-19 | | 0.2x(x+3)-4(2x-3)=0.9 | | y+258=-8y-3 | | 7.50+2.50b=12.50 |

Equations solver categories